STUDY ON SHORT CIRCUIT ELECTRICAL SYSTEM PT. PLN (Persero) SULSELBAR - Rais, Muhammad; Astuty, Astuty (Department of Electrical Engineering, University of Patria Artha, 2017)
In the electric power system, the short-circuit study is essential for planning, designing and extending the electrical system. The data obtained from this calculation will be used to determine busbar tuning and power breaker capacity. The circuit breaker selection for the electrical power system depends not only on the current flowing in the circuit breaker in a normal working state but also on the maximum current that may flow over time and on the current which may have to be decided at the channel voltage where the breaker is located. Disturbance to the electrical system causes the operation of relays and power breakers to decide which parts are experiencing interference. The three phase short circuit is considered to be the interference with the largest disturbance current compared to other interference. While the one-phase short circuit to the ground is a common disorder, especially in the airways. The objective of this research is to analyze the short circuit current of power system of South and West Sulawesi with the condition of the system working at peak load and condition when all the system generator operate. The rail impedance matrix method is used in the calculation of the noise current with the matlab computation tool. Compared with the three-phase interference, the larger one-phase current to the ground is 1.065 times three phase short circuit for maximum peak load state, and 1,233 times three phase short circuit for all active generators.Â